Zabrocki’s structural phonetics in the case study of velar POA assimilation in Latinate prefixation in RP English - Haładewicz-Grzelak, Małgorzata (Lingua Posnaniensis, 2014)
Zabrocki understood structural phonetics as a branch of phonetics concerned with analyzing acodal (substantial) systems (cf. Bańczerowski 1980: 13). In this theory, each sound has a specific acoustic and articulatory substance. Zabrocki constructed linear substantial sound structures based on measuring the amount of substance implied in the articulation. Diachronic structural phonetics, in turn, is the application of synchronically defined phonetic and acoustic relations to the study of language change. This paper investigates a synchronic scenario for velar POA assimilation in Latinate prefixation in English and tests the findings against the tenets of Zabrocki’s theory. The results show that Zabrocki’s structural phonetics perfectly accounts for the empirical findings. The corpus of investigation is comprised of realizations of all RP English Latinate prefixes ending with /n/, collected from various pronunciation dictionaries (online and paper). As a collateral corpus, recordings of two native speakers of English were made in which they produced some of the corpus material, as well as nonce words and unusual lexemes not listed in pronunciation dictionaries